Study of the Semantic (Thematic) Group "Personal Jewelry" in Armenian Dialects - Ghamoyan, Lusine (Bulletin of Yerevan University B: Philology, 2024)
While studying the words expressing the concept "personal jewelry" in Armenian dialects, we noticed that the latter mostly did not preserve the Indo-European word names, instead of them borrowed (Persian, Turkish, Arabic, etc.) names were used, which are not recorded in a number of dictionaries at our disposal (etymological and loanwords), and their origin is mostly unknown. In the course of the study we tried to divide the names of precious, semi-precious and priceless jewelry by classifying many dialect names into separate groups expressing the concepts of bracelet, earrings, necklace, ring, head-ornament and noticed that some of the names can be used simultaneously for different parts of the body or clothing. We paid attention to homonymic series (more than 2 dozens), in which only one of the members is a word denoting the concept "jewelry". We also revealed that some names of jewelry in Armenian dialects were and are still used as magical means (for protection from evil). In the work, close attention is paid to many popular proverbs and phraseological units with the names of ornaments, which are still used by the society.